Synthesis of Carbamate-Modified Cellulose Biocoagulant from Jengkol (Archidendron pauciflorum) Peel via Crosslinking Method for Lead Removal from Wastewater - Alpan Sofyan Tanjung; Rifda Adillah; Muhammad Fajrul Rahman; Yulia Eka Putri (ALCHEMY Jurnal Penelitian Kimia, 2026)
Heavy metal pollution poses a serious environmental and health threat. An effective and environmentally friendly solution to mitigate this issue is the use of cellulose-based coagulants derived from jengkol (Archidendron pauciflorum) peel waste modified with carbamates. Cellulose isolated from jengkol peel was successfully modified with carbamate derived from urea through a crosslinking method. The formation of cellulose and carbamate crosslinks was confirmed by Fourier transform infrared (FTIR) spectroscopy, which showed new absorption peaks corresponding to amide (–NH2) and nitrile (CN) functional groups. Morphological observations using a scanning electron microscope (SEM) showed changes in the shape of cellulose fibers after modification with carbamate, where carbamate cellulose exhibited a denser fiber morphology with larger pore sizes. Elemental analysis revealed the presence of nitrogen in carbamate-crosslinked cellulose, indicating that the cellulose has successfully bonded with the carbamate derived from urea. The decrease in heavy metal lead (Pb) concentration in wastewater samples was achieved by adding 1.5 g of carbamate-modified cellulose, resulting in 96.87% Pb removal. These results show that the cellulose-based biocoagulant from jengkol peel waste, modified with carbamate via crosslinking, has been successfully synthesized and significantly reduced the concentration of the heavy metal Pb.